Neutrosophic Decision Framework for Performance Analysis in Construction Project Management Using the EVAMIX Method - Jiao Wang (Neutrosophic Sets and Systems)
The performance evaluation of construction project management is the process of comprehensively assessing the effectiveness and efficiency of project management based on key indicators such as cost, schedule, quality, and safety. Through quantitative analysis and comprehensive evaluation, it identifies strengths and weaknesses in management, ensuring the achievement of project goals and providing references for future improvements. This evaluation not only helps optimize resource allocation but also enhances the overall level of project management, ensuring the project is completed on time, with quality, and efficiently. The performance evaluation of construction project management is multiple-attribute decision-making (MADM). Currently, the EVAMIX approach is employed to implement MADM. The type-2 neutrosophic sets (T2NSs) are administrated as an efficient approach for manipulating uncertain information during the performance evaluation of construction project management. In this paper, the type-2 neutrosophic number EVAMIX (T2NN-EVAMIX) approach is administrated for MADM. The average approach is to put forward weight information with T2NSs. Finally, a numerical example for performance evaluation of construction project management is administrated and some efficient comparisons are found to verify the T2NN-EVAMIX approach. The major contribution of this paper is administrated: (1) The average approach is utilized to manage the weight numbers based on T2NSs; (2) the T2NN-EVAMIX approach is administrated for MADM under T2NSs; (3) Finally, a numerical example for performance evaluation of construction project management is administrated and (4) some comparisons are administrated to show some advantages of T2NN-EVAMIX approach.